2018
DOI: 10.5194/adgeo-45-19-2018
|View full text |Cite
|
Sign up to set email alerts
|

Mortar mixes with oxblood: historical background, model sample recipes and properties

Abstract: Abstract. In this survey we present studies on mortar mixes added with oxblood, which was a commonly found local waste material, with a wide application and long history of use; a precise recipe of lime–pozzolan mortar with blood addition from a 19th-century Italian manual was chosen, and model samples were prepared accordingly, with the aim of better understanding the chemical, mineralogical and physical characteristics of such compositions, starting with a blank reference specimen. The specimens were analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and thermogravimetry (TGA) analysis results suggested that all amino acids displayed the ability of calcite inhibition and amorphous calcium carbonate (ACC) facilitation, but to different degrees. It is intriguing to note that the effect revealed by a single amino acid can be similar to that of whole proteins, since in our previous studies on lime-based mortars with oxblood addition, the formation of ACC in mortars with oxblood addition was also confirmed by FTIR, XRD, TG-DSC and SEM analyses [12,51,52]. It was speculated in these previous studies that ACC stabilization could be realized through lowered supersaturation in solution by combination between calcium ions and protein sections rich in glutamic acid, serine, glycine, and carbohydrates.…”
Section: Discussionmentioning
confidence: 82%
“…Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD) and thermogravimetry (TGA) analysis results suggested that all amino acids displayed the ability of calcite inhibition and amorphous calcium carbonate (ACC) facilitation, but to different degrees. It is intriguing to note that the effect revealed by a single amino acid can be similar to that of whole proteins, since in our previous studies on lime-based mortars with oxblood addition, the formation of ACC in mortars with oxblood addition was also confirmed by FTIR, XRD, TG-DSC and SEM analyses [12,51,52]. It was speculated in these previous studies that ACC stabilization could be realized through lowered supersaturation in solution by combination between calcium ions and protein sections rich in glutamic acid, serine, glycine, and carbohydrates.…”
Section: Discussionmentioning
confidence: 82%
“…40 Similar results are observed in Khouzani et al., 58 where the band at 713 cm −1 appears after the DSC measurement with a final temperature of 400 °C. According to the SEM images in Zhang et al., 4 rhombohedral calcite particles can be clearly distinguished in specimen B; while in specimens A, C, and D the CaCO 3 particles appear to be rounded, which could further indicate the presence of amorphous calcium carbonate in these specimens.…”
Section: Discussionmentioning
confidence: 90%
“…By an historical point of view, for instance, the addition of blood in mortars was described by Rutilius Palladius in Opus Agriculturae at around the fourth to fifth century A.D., 3 as hot and cold maltha for baths. Geographically speaking, animal blood was applied in mortars in many parts of the world, such as in Europe and Asia, 4 as well as in the American continents. 5…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jasiczak and Zieliński [16] conducted tests of the effect of protein additives, such as chicken and bovine blood (red cells) on the properties of cement mortar. In a similar vein, Fang et al [17] and Zhang et al [18] had recently brought up a topic of properties of traditional Chinese lime mortars with oxblood as an ingredient, which showed that lime mortars with oxblood exhibited better bonding strength and weather resistance (including waterproof quality) than regular lime mortar. The research conducted by Zhao et al [19] showed that pig blood had a similar beneficial effect on properties, such as early strength.Modifications of mortar with fibers constitute a separate research group.…”
mentioning
confidence: 96%